Teachers’ Perspectives on Repetition as a Cognitive Strategy in Teaching English Vocabulary to Junior High School Students - Yani Lubis; Nadila Adelia Putri; Najla Regar; Juanda Muktar Hasibuan (Jurnal Ilmiah Multidisiplin, 2026)
This study explores English teachers’ perspectives on the use of repetition as a cognitive strategy in teaching vocabulary to junior high school students. Employing a qualitative descriptive design, data were collected through six in-depth interviews, classroom observations, and document analysis involving two experienced English teachers from a junior high school in Helvetia, North Sumatra. The novelty of this research lies in highlighting teachers’ viewpoints as the central lens for understanding how repetition functions cognitively and pedagogically in EFL classrooms. The findings reveal that teachers perceive repetition as a meaningful process that reinforces students’ memory and facilitates vocabulary retention through contextual and varied practice. Despite challenges in maintaining engagement, repetition was viewed as an effective and adaptable strategy that bridges psycholinguistic theory and classroom application. The study contributes to a deeper understanding of how cognitive principles can inform vocabulary teaching practices in EFL contexts.